Dis/abled Student Campusmaking: Sites of New Possibility - Eddie Comeaux; Danielle Mireles; Anna Acha (MDPI AG, 2021)
Scholars have attempted to reveal the structural barriers that dis/abled students cope with and navigate during college, but it remains unclear how these students interpret their experiences on campus and what strategies they employ to manage and respond to unsupportive and hostile campus climates. In this paper, we describe freedom movements that sought to secure equal access to opportunities and rights for people with dis/abilities, and we highlight and explain forms of resistance among d/Deaf and dis/abled postsecondary students. To do so, we draw on dis/ability critical race theory and also advance the concept of campusmaking, which refers to the ways that students navigate complex campus spaces and create sites of togetherness and resistance. We discuss broader structural and climate issues facing college students with dis/abilities, particularly those who are Black, Indigenous, and people of color. In so doing, we gain insight into dis/abled student campusmaking amid and in spite of ableist and racist postsecondary contexts. We conclude with a discussion of the gaps in existing research and the questions that warrant further study.